2018
DOI: 10.5530/ajbls.2018.7.10
|View full text |Cite
|
Sign up to set email alerts
|

DPPH Radical Scavenging Potential of Ginger Leaves and Rhizomes

Abstract: Introduction: Gingers, belonging to the family Zingiberaceae, are popularly known for their beneficial uses in medicine and culinary applications. Aim: This study was conducted to evaluate the DPPH radical scavenging activity of the leaves and rhizomes of Zingiber officinale Rosc., Curcuma longa L., and Etlingera elatior (Jack) R.M. Smith. Methods: The plant samples were collected from Bukidnon, Mindanao, Philippines. Both water and ethanolic extracts were prepared separately from its leaves and rhizomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some have already been authorized as food additives or flavorings, while others are presently being evaluated. Scientists are currently examining the possibility of encapsulating essential oils to stabilize and even enhance their antioxidant properties (61)(62)(63). Generally, rhizome essential oils and their derivatives have displayed their potential as biopreservatives, improving the physicochemical and organoleptic features of food ingredients, including meat, vegetables, and other agricultural and fishery products, either on their own or in combination with other plant extracts (64).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some have already been authorized as food additives or flavorings, while others are presently being evaluated. Scientists are currently examining the possibility of encapsulating essential oils to stabilize and even enhance their antioxidant properties (61)(62)(63). Generally, rhizome essential oils and their derivatives have displayed their potential as biopreservatives, improving the physicochemical and organoleptic features of food ingredients, including meat, vegetables, and other agricultural and fishery products, either on their own or in combination with other plant extracts (64).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This has been demonstrated in studies where an edible coating made from achira starch (Canna indica L.) and containing 0.5% w/w turmeric rhizome oil reduced the growth of common pumpkin destructive fungi Penicillium and Cladosporium spp. by 41.6-60.3% for up to 15 days (62). The essential oil from turmeric rhizome has also been found to have antifungal properties against Aspergillus spp., including the common contaminant A. flavus found in cereals, legumes, juices, and fresh and dried fruits (79,80).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Isolation of Zingiberene, 1,8 cineole, camphor, camphene and borneol investigation for potent cardiotonic effect was done. [55] Anti-viral activity Germacrone and Curcumin were isolated from C. zedoaria rhizome to study for antiviral activity against H1N1, HSV-1 and it showed good antiviral potential. [57]…”
Section: Cardiotonic Activitymentioning
confidence: 99%
“…Antioxidant properties of some chemical compounds can prevent or reduce cell damage caused by free radicals and the effects of reactive oxygen species (ROS), which are continuously formed by the body when using oxygen to process metabolic functions such as respiration and some cell-mediated immune functions (Tohma et al, 2017). Antioxidant components are necessary to protect the human body from oxidative cell damage, which is correlated with some diseases, preserve cell components in a reduced state, and improve health by preventing degenerative diseases (Barbosa and Peteros, 2018).…”
Section: Introductionmentioning
confidence: 99%